More challenges ahead—metabolic heterogeneity of pancreatic cancer stem cells. (3rd March 2016) - Heeschen, Christopher; Sancho, Patricia
ABSTRACT: Pancreatic cancer stem cells (CSCs) display a distinct metabolic phenotype based on their strong dependence on mitochondrial oxidative phosphorylation (OXPHOS) and limited metabolic plasticity. While suppression of MYC upstream of PGC-1α was the key determinant of this phenotype, we also identified a subset of CSCs with reduced mitochondrial content that showed resistance to mitochondrial targeting, but could be sensitized by inhibition of MYC.